2017
DOI: 10.1371/journal.pone.0178809
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly and quantification reveal differentially expressed genes between soft-seed and hard-seed pomegranate (Punica granatum L.)

Abstract: Pomegranate (Punica granatum L.) belongs to Punicaceae, and is valued for its social, ecological, economic, and aesthetic values, as well as more recently for its health benefits. The ‘Tunisia’ variety has softer seeds and big arils that are easily swallowed. It is a widely popular fruit; however, the molecular mechanisms of the formation of hard and soft seeds is not yet clear. We conducted a de novo assembly of the seed transcriptome in P. granatum L. and revealed differential gene expression between the sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 28 publications
2
42
1
Order By: Relevance
“…We also identified many transcription factor families, such as MYB (16 genes), WRKY (five genes), AP2‐like (16 genes), MYC (two genes) and NAC (nine genes), that contained different proportions of SNPs and InDels (Figure b). Most of these transcription factors have been reported to play roles in regulating the seed hardness of pomegranates (Luo et al ., ; Xue et al ., ) and hawthorns (Dai et al ., ). In the comparison between ‘Tunisia’ and ‘Sanbai’, we detected a SNP (T‐C) at the 166‐bp position of the NAC ( PgL0137670 ) transcription factor coding sequence.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We also identified many transcription factor families, such as MYB (16 genes), WRKY (five genes), AP2‐like (16 genes), MYC (two genes) and NAC (nine genes), that contained different proportions of SNPs and InDels (Figure b). Most of these transcription factors have been reported to play roles in regulating the seed hardness of pomegranates (Luo et al ., ; Xue et al ., ) and hawthorns (Dai et al ., ). In the comparison between ‘Tunisia’ and ‘Sanbai’, we detected a SNP (T‐C) at the 166‐bp position of the NAC ( PgL0137670 ) transcription factor coding sequence.…”
Section: Resultsmentioning
confidence: 97%
“…For example, gene expression analyses revealed that lignin and cellulose biosynthetic genes, including CCR, CAD, CelSy, SuSy, CCoA-OMT, MYB, WRKY and MYC, are differentially expressed between soft-and hard-seeded pomegranate varieties at different growth stages (e.g. fruit setting to ripening stages) (Xue et al, 2017;Zarei et al, 2016). Quantitative proteomics and microRNA sequencing results have suggested that genes altering the cell wall structure contribute to the differences in seed hardness between soft-and hard-seeded pomegranates (Luo et al, 2018;Niu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The texture of the inner seed coat greatly affects acceptability to consumers. The preference of most consumers for soft-seeded pomegranates has accelerated the breeding of soft-seeded pomegranate cultivars and promoted mechanistic studies of the development of soft inner seed coats [2][3][4][5] . However, a complete overview of seed coat development in pomegranate has not yet been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the best-known commercial soft-seeded pomegranate variety is Tunisia. This variety has been cultivated in China for more than 30 years 4 , resulting in cultivar depression. Thus, breeding new soft-seeded cultivars is imperative to meet market demands.…”
Section: Introductionmentioning
confidence: 99%